Interreligious encounters in polemics between Christians, Jews, and Muslims in Iberia and beyond - García-Arenal, Mercedes; Wiegers, Gerard Albert; Szpiech, Ryan (Brill, 2018)
"This book discusses the "long fifteenth century" in Iberian history, between the 1391 pogroms and the forced conversions of Aragonese Muslims in 1526, a period characterized by persecutions, conversions and social violence, on the one hand, and cultural exchange, on the other. It was a historical moment of unstable religious ideas and identities, before the rigid turn taken by Spanish Catholicism by the middle of the sixteenth century; a period in which the physical and symbolic borders separating the three religions were transformed and redefined but still remained extraordinarily porous. The collection argues that the aggressive tone of many polemical texts has until now blinded historiography to the interconnected nature of social and cultural intimacy, above all in dialogue and cultural transfer in later medieval Iberia. Contributors are Ana Echevarría, Gad Freudenthal, Mercedes García-Arenal, Maria Laura Giordano, Yonatan Glazer-Eytan, Eleazar Gutwirth, Felipe Pereda, Rosa M. Rodríguez Porto, Katarzyna K. Starczewska, John Tolan, Gerard Wiegers, and Yosi Yisraeli"--